2019
DOI: 10.1371/journal.pone.0225529
|View full text |Cite
|
Sign up to set email alerts
|

A daily diary study on maladaptive daydreaming, mind wandering, and sleep disturbances: Examining within-person and between-persons relations

Abstract: Cross-sectional and experimental research have shown that task-unrelated thoughts (i.e., mind wandering) relate to sleep disturbances, but there is little research on whether this association generalizes to the day-level and other kinds of task-unrelated mentation. We employed a longitudinal daily diary design to examine the within-person and between-person associations between three self-report instruments measuring mind wandering, maladaptive daydreaming (a condition characterized by having elaborate fantasy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 44 publications
2
26
0
1
Order By: Relevance
“…Additionally, we cannot draw causal inferences from any observed association with sleep disturbances. Regarding the temporal association between mind wandering and sleep, a recent longitudinal study indicated that self-reported sleep disturbances on the night are likely to be followed by increased mind wandering the next day, but the study did not find a significant reversed association between mind wandering on the day and sleep disturbances the next night 49 . A second limitation of the present study is the use of self-reports for measuring sleep disturbances and mind wandering.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, we cannot draw causal inferences from any observed association with sleep disturbances. Regarding the temporal association between mind wandering and sleep, a recent longitudinal study indicated that self-reported sleep disturbances on the night are likely to be followed by increased mind wandering the next day, but the study did not find a significant reversed association between mind wandering on the day and sleep disturbances the next night 49 . A second limitation of the present study is the use of self-reports for measuring sleep disturbances and mind wandering.…”
Section: Discussionmentioning
confidence: 87%
“…It is possible, however, that waking up to respond to the nighttime probes significantly affected sleep quality or the phenomenological qualities of dreams or waking thoughts. Given that previous work has found a link between sleep disturbance and mind wandering (Marcusson-Clavertz, West, Kjell, & Somer, 2019), it will be important for future iterations of this study to examine and, if possible, protect against, this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that sleep disturbances in soldiers before deployment predicted the degree of re-experiencing symptoms post-deployment [73]. Studies recording day-to-day variations in sleep have found that participants with PTSD had increased intrusion symptomology after nights with shorter sleep duration [74], and that mindwandering in general increases after nights with poor sleep [75].…”
Section: Factors During Sleep That Make Memories More or Less Intrusivementioning
confidence: 99%